Cross-country evidence on the impact of decentralisation and school autonomy on educational performance and school autonomy on educational performance - Lastra Anadón, Carlos; Mukherjee, Sonia (OECD Publising, 2019)
How do administrative and fiscal decentralisation relate to education system performance? The question is answered by exploiting a panel with several different measures of fiscal decentralisation: a measure of administrative decentralisation, as well as a measure of school autonomy (using six waves of PISA). These measures are related to educational outcomes, measured by PISA score country averages. The panel includes year fixed effects and multiple country covariates. Overall, a positive relationship is found linking administrative and fiscal decentralisation with performance, as measured by PISA tests. School autonomy is also positively related with educational outcomes, strengthening the estimated effects of administrative and fiscal decentralisation.
Keywords: Educational performance; Public governance; Public sector productivity; Intergovernmental relations; 58 Pedagogía::5802 Organización y planificación de la educación; ODS 4 - Educación de calidad